Thermoplastic plastic blend material with enhanced interfacial compatibility and thermal stability and process for preparing the same
Patent Information
- Application Number
- CN202611123383.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的在于提供一种具有增强界面相容性与热稳定性的热塑性塑胶共混材料及其制备工艺,以解决背景技术中提出的现有共混材料界面相容性不足、熔融降解风险高以及工艺温控精度不够的问题
[0026]1.通过引入超支化聚合物接枝的纳米二氧化硅(SiO2-g-HBP)为界面改性剂,利用其三维支化结构渗透入聚合物界面,纳米二氧化硅的刚性核提供物理锚点,而末端长链结构与基体发生分子链缠结,实现了化学与物理双重增容,显著降低界面张力,提升共混结构的稳定性与力学性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of plastic materials technology, and more specifically, to a thermoplastic blend material with enhanced interfacial compatibility and thermal stability, and its preparation process. Background Technology
[0002] Thermoplastic blends are widely used in many fields due to their recyclability and ease of processing. However, in existing technologies, a series of challenges are often faced when blending different polymers (such as polylactic acid and thermoplastic polyurethane).
[0003] In the prior art, Chinese patent application publication number CN116656101A discloses a thermoplastic plastic blend material and its preparation process. The formula includes: polylactic acid, thermoplastic polyurethane, toluene diisocyanate, MDI, graphite, zinc stearate, solubilizer, defoamer, and chain extender; the weight parts of each component are: 50-60 parts of polylactic acid, 47-53 parts of thermoplastic polyurethane, 8-12 parts of toluene diisocyanate, 15-21 parts of MDI, 6-10 parts of graphite, ... This invention, comprising 2-4 parts zinc stearate, 12-18 parts solubilizer, 3-5 parts defoamer, and 1-3 parts chain extender, removes the carbonized layer on the surface of the raw materials through pretreatment, shortens the residence time in the molten state, avoids material degradation, and improves the mechanical properties of the material. Preheating the screw extruder prevents temperature changes during processing from affecting the overall quality of the material. Adding solubilizer during blending improves the stability of the blended structure, reduces preparation difficulty, and ensures a high production yield. The existing technology has the following technical problems: Firstly, significant differences in surface tension between different materials lead to poor interfacial compatibility, making it difficult to uniformly disperse the components in the formulation, thus affecting the mechanical properties and service life of the final product. Secondly, the existing process lacks precision in preheating and temperature control before extrusion, resulting in excessively long residence time in the molten state, which easily triggers thermal degradation of the material, further reducing material performance and affecting batch consistency.
[0004] To address the aforementioned issues, numerous studies in the prior art have focused on improving the compatibility and processing stability of PLA / TPU blends. However, in industrial production, the synergistic effect and stability of specific formulation systems (such as PLA and TPU) still need further improvement. In particular, how to achieve efficient interfacial compatibilization while simultaneously reducing the risk of melt degradation and improving batch consistency remains a pressing technical challenge in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a thermoplastic blend material with enhanced interfacial compatibility and thermal stability, and its preparation process, in order to solve the problems of insufficient interfacial compatibility, high risk of melt degradation, and insufficient process temperature control accuracy of existing blend materials mentioned in the background art.
[0006] A thermoplastic blend material with enhanced interfacial compatibility and thermal stability comprises, by weight, the following raw material formulation: 50-60 parts of polylactic acid (PLA), 47-53 parts of thermoplastic polyurethane (TPU), 8-12 parts of toluene diisocyanate, 15-21 parts of diphenylmethane diisocyanate (MDI), 6-10 parts of graphite, 2-4 parts of zinc stearate, 12-18 parts of solubilizer, 3-5 parts of defoamer, 1-3 parts of chain extender, and 1-5 parts of nano-interfacial modifier.
[0007] Preferably, the nano-interface modifier is nano-silica (SiO2-g-HBP) grafted with a hyperbranched polymer; the hyperbranched polymer is a hyperbranched polyester with long-chain aliphatic groups at the ends.
[0008] Preferably, the solubilizer is composed of polysorbate 20, polysorbate 60 and fatty acid polyoxyethylene ester, and the weight ratio of polysorbate 20, polysorbate 60 and fatty acid polyoxyethylene ester is 1:1:3.
[0009] Preferably, the nano-interface modifier and the solubilizer work synergistically to reduce interfacial tension.
[0010] Preferably, the polylactic acid comprises 55 parts by weight and the thermoplastic polyurethane comprises 50 parts by weight.
[0011] Explanation of the functional division and mechanism of action of each key component:
[0012] The technical solution of this invention is not a simple superposition of multiple known components, but rather a clear division of functions and synergistic effects among the components. Specifically:
[0013] Solubilizer (12-18 parts): In this invention, it is mainly responsible for the physical dispersion in the first stage. In the early stage of melt blending (step four), it rapidly reduces the interfacial tension between the PLA and TPU phases, promoting the initial uniform distribution at the macroscopic level.
[0014] Nanoscale interface modifier (SiO2-g-HBP, 1-5 parts): Its role extends throughout subsequent stages, primarily responsible for the chemical bonding and physical anchoring in the second stage. Its hyperbranched terminal active groups can react in situ with the PLA / TPU interface, achieving chemical compatibilization; simultaneously, the rigid core of nano-silica provides physical anchoring points, forming molecular chain entanglement with the matrix, thus achieving permanent and stronger interface enhancement, far exceeding the effect of single physical dispersion or single chemical compatibilization. This nanoscale interface modifier and solubilizer have a significant synergistic effect in reducing interfacial tension; the combined effect far exceeds the simple sum of the effects of using either alone.
[0015] The division of labor between toluene diisocyanate and diphenylmethane diisocyanate (MDI):
[0016] The toluene diisocyanate added in step three mainly acts as a rapid chain extender. During the reactive compatibilization stage, it preferentially reacts with the PLA / TPU chain ends, rapidly increasing the molecular weight.
[0017] The MDI added in step four mainly serves as a long-chain compatibilizer / crosslinking agent. Its bifunctional aromatic structure has better compatibility with various components and can more effectively form a flexible crosslinking network at the interface between two phases, thereby improving interfacial strength without sacrificing elongation.
[0018] This invention also provides a process for preparing the above-mentioned thermoplastic blend material with enhanced interfacial compatibility and thermal stability, comprising the following steps:
[0019] Step 1, Weighing raw materials: Weigh each raw material according to the weight proportions of each component and set aside;
[0020] Step 2, Pre-treatment: The polylactic acid and thermoplastic polyurethane prepared in Step 1 are placed in a cleaning tank for repeated rinsing and ultrasonic cleaning, followed by drying to obtain pre-treated raw materials.
[0021] Step 3, Melting and Reactive Compatibilization: The pretreated raw materials are placed in a reactor and heated to 180-190°C. Then, the toluene diisocyanate, defoamer, chain extender, and nano-interface modifier prepared in Step 1 are added, and the mixture is stirred at high speed under constant temperature. During this process, the active groups at the ends of the hyperbranched polymer react in situ with the PLA / TPU interface, achieving chemical compatibilization. Simultaneously, the toluene diisocyanate exerts a rapid chain-extending effect. Rheometer measurements show that the melting residence time at 185°C in this invention's process does not exceed 35 seconds, significantly lower than the 2-3 minutes of the traditional process, thus effectively reducing thermal degradation.
[0022] Step 4, blending and dispersion: Pour the molten material obtained in step 3 into a mixing tank, add MDI and solubilizer, and continue stirring at 170-173℃ to obtain a blended material; In this stage, MDI plays a role in long-chain compatibilization / crosslinking, and the solubilizer plays a role in physical dispersion to reduce interfacial tension.
[0023] Step 5, conditioning and functionalization: Pour the blend material obtained in step 4 into the reaction tower, add graphite and zinc stearate, and perform bottom blowing stirring and heat preservation under argon protection to obtain the extrusion raw material;
[0024] Step 6, Dynamic temperature-controlled extrusion molding based on online rheological feedback: The extrusion material prepared in Step 5 is fed into a screw extruder equipped with an online rheometer and a near-infrared spectral sensor; the system dynamically adjusts the temperature of the barrel section and the extrusion section of the extruder according to the online monitored melt viscosity and component uniformity data; preferably, the barrel section temperature is 165-168℃, the extrusion section temperature is 180-183℃, and the screw speed of the screw extrusion is 150 r / min; after preheating, screw extrusion is performed, and the final product is obtained after cutting.
[0025] The beneficial effects of this invention are as follows:
[0026] 1. By introducing hyperbranched polymer-grafted nano-silica (SiO2-g-HBP) as an interface modifier, its three-dimensional branched structure penetrates into the polymer interface. The rigid core of the nano-silica provides physical anchor points, while the long-chain structure at the end forms molecular chain entanglement with the matrix, achieving dual compatibilization through chemical and physical processes, significantly reducing interfacial tension, and improving the stability and mechanical properties of the blend structure.
[0027] 2. The introduction of hyperbranched polymers reduces melt viscosity. Combined with the optimized multi-stage temperature control strategy of this process, the melt residence time is effectively shortened (measured to be no more than 35 seconds at 185°C), reducing the risk of thermal degradation and ensuring the mechanical properties of the prepared material. Thermogravimetric analysis (TGA) tests show that the thermal decomposition temperature of the blend material of this invention is approximately 15°C higher than that of the control group within the processing temperature range, demonstrating its excellent thermal stability.
[0028] 3. The dynamic temperature control extrusion process based on online rheological feedback can sense and compensate for temperature fluctuations in real time, ensuring precise and stable temperature during the extrusion molding process. Compared with traditional open-loop preheating control, it significantly improves batch consistency and overall quality of products. Detailed Implementation
[0029] To further understand the features, technical means, and specific objectives and functions achieved by the present invention, a more detailed description is provided below in conjunction with specific embodiments.
[0030] Example 1
[0031] Weigh out 55 parts PLA, 50 parts TPU, 10 parts toluene diisocyanate, 18 parts MDI, 8 parts graphite, 3 parts zinc stearate, 15 parts solubilizer (polysorbate 20, polysorbate 60 and fatty acid polyoxyethylene ester mixed in a ratio of 1:1:3), 4 parts defoamer, 2 parts chain extender, and 3 parts nano-interface modifier (SiO2-g-HBP).
[0032] PLA and TPU were ultrasonically cleaned and dried. The pretreated raw materials were then fed into a reactor, heated to 185°C, and defoamer, chain extender, toluene diisocyanate, and nano-interface modifier were added. The mixture was stirred at high speed to promote reactivity. The melt was then transferred to a mixing tank, where MDI and a solubilizer were added, and the mixture was continuously stirred at 172°C. Next, the material was transferred to a reaction tower, where graphite and zinc stearate were added, and the mixture was bottom-blown and kept warm under argon protection. Finally, the material was fed into a screw extruder equipped with an online rheometer and a near-infrared spectroscopy sensor. The barrel section temperature was controlled at 166°C, and the extrusion section temperature was controlled at 182°C. The material was extruded at a screw speed of 150 rpm and then cut to obtain the final product.
[0033] Definition of performance test and control group:
[0034] All performance improvement percentages and data comparisons below are based on blank PLA / TPU blends with the same formulation but without the addition of nano-interface modifiers and solubilizers.
[0035] Basic performance testing: The material prepared in this embodiment was subjected to performance testing. The results showed that, compared with the blank control group, its interfacial tension was significantly reduced, tensile strength increased by about 25%, elongation at break increased by about 30%, and thermal stability testing showed that its thermal decomposition temperature was increased by about 15°C compared with the control group. Furthermore, through online rheological monitoring, the viscosity fluctuation coefficient of 100 batches of products produced continuously was controlled within ≤3%.
[0036] Synergistic effect test: To verify the synergistic effect of the nano-interface modifier (SiO2-g-HBP) and solubilizer in reducing interfacial tension, the following control experiments were conducted separately:
[0037] Experiments using 15 parts of solubilizer (without SiO2-g-HBP) alone showed that the interfacial tension decreased by 8%.
[0038] Experiments using 3 portions of SiO2-g-HBP (without solubilizer) alone showed a 6% reduction in interfacial tension.
[0039] When the two are used together (i.e., the formulation of Example 1), the reduction is 18%.
[0040] Test results confirmed that 18% > 8% + 6% = 14%, demonstrating that the nano-interface modifier and solubilizer have a significant synergistic effect in reducing interfacial tension.
[0041] Comparative Example 1: No nano-silica was used; only hyperbranched polymers were used.
[0042] Formulation: Same as Example 1, containing 15 parts solubilizer, but replacing 3 parts of nano-interface modifier (SiO2-g-HBP) with an equal amount of pure hyperbranched polymer.
[0043] Process: Same as in Example 1.
[0044] Performance Comparison: Compared with Example 1, the interfacial tension of the material prepared in this comparative example is slightly reduced, but the tensile strength is only increased by about 10%, and the elongation at break is increased by about 15%. This indicates that without the rigid core of nano-silica as a physical anchor, the entanglement effect of hyperbranched polymers alone is limited and cannot achieve optimal mechanical reinforcement.
[0045] Comparative Example 2: No grafting was performed; only nano-silica was used.
[0046] Formulation: Same as Example 1, containing 15 parts of solubilizer, but replacing 3 parts of nano-interface modifier (SiO2-g-HBP) with an equal amount of unmodified nano-silica.
[0047] Process: Same as in Example 1.
[0048] Performance Comparison: Compared with Example 1, the material prepared in this comparative example showed only a slight improvement in interfacial tension, an increase in tensile strength of approximately 5%, and almost no change in elongation at break. This indicates that ungrafted nano-silica exhibits poor dispersion in the polymer matrix and lacks active groups that can chemically bond with the matrix, thus failing to provide effective compatibilization and reinforcement.
[0049] Comparative Example 3: Using the conventional compatibilizer E-GMA
[0050] Formulation: Same as Example 1, containing 15 parts of solubilizer, but replacing 3 parts of nano-interface modifier (SiO2-g-HBP) with an equal amount of E-GMA.
[0051] Process: Same as in Example 1.
[0052] Performance Comparison: Compared to Example 1, the material prepared in this comparative example showed some improvement in interfacial tension and mechanical properties, but the tensile strength increased by only about 15%, and the elongation at break increased by about 20%. More importantly, the viscosity fluctuation coefficient of the system using E-GMA during continuous production was ±5%, exhibiting worse batch stability compared to Example 1 (≤3%). This indicates that traditional compatibilizers cannot provide the dual (physical + chemical) interfacial strengthening effect and the improvement in processing stability offered by SiO2-g-HBP.
[0053] All performance improvement percentages in this invention are based on blank PLA / TPU blends using the same formulation but without the addition of nano-interface modifiers and solubilizers.
[0054] Summary of Results
[0055]
[0056] The comparative experiments above quantitatively demonstrate that the "hyperbranched polymer-grafted nano-silica (SiO2-g-HBP)" used in this invention is not a simple sum of the functions of hyperbranched polymers and nano-silica, but rather produces a synergistic effect where 1+1>2. This synergistic effect is significantly superior to solutions using only a single component or traditional compatibilizers, strongly refuting the criticism of "simple combination." In summary, the solution of this invention exhibits significant improvements in interfacial tension, mechanical properties, thermal stability, and batch-to-batch consistency, possessing outstanding substantive characteristics.
[0057] The embodiments described above merely illustrate the optimal implementation of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A thermoplastic blend material with enhanced interfacial compatibility and thermal stability, characterized in that, By weight, its raw material formulation includes: 50-60 parts of polylactic acid, 47-53 parts of thermoplastic polyurethane, 8-12 parts of toluene diisocyanate, 15-21 parts of diphenylmethane diisocyanate, 6-10 parts of graphite, 2-4 parts of zinc stearate, 12-18 parts of solubilizer, 3-5 parts of defoamer, 1-3 parts of chain extender, and 1-5 parts of nano-interface modifier.
2. The thermoplastic blend material with enhanced interfacial compatibility and thermal stability according to claim 1, characterized in that, The nano-interface modifier is nano-silica grafted with a hyperbranched polymer; the hyperbranched polymer is a hyperbranched polyester with long-chain aliphatic groups at the ends.
3. The thermoplastic blend material with enhanced interfacial compatibility and thermal stability according to claim 1, characterized in that, The solubilizer is composed of polysorbate 20, polysorbate 60 and fatty acid polyoxyethylene ester, and the weight ratio of polysorbate 20, polysorbate 60 and fatty acid polyoxyethylene ester is 1:1:
3.
4. The thermoplastic blend material with enhanced interfacial compatibility and thermal stability according to claim 1, characterized in that, The nano-interface modifier and the solubilizer work synergistically to reduce interfacial tension.
5. The thermoplastic blend material with enhanced interfacial compatibility and thermal stability according to claim 1, characterized in that, The polylactic acid comprises 55 parts by weight, and the thermoplastic polyurethane comprises 50 parts by weight.
6. A process for preparing a thermoplastic blend material with enhanced interfacial compatibility and thermal stability as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1, Weighing raw materials: Weigh each raw material according to the weight proportions of each component and set aside; Step 2, Pre-treatment: The polylactic acid and thermoplastic polyurethane prepared in Step 1 are placed in a cleaning tank for repeated rinsing and ultrasonic cleaning, followed by drying to obtain pre-treated raw materials. Step 3, melt mixing and reactive compatibilization: Place the above pretreated raw materials into a reaction vessel, heat to 180-190°C, and then add the toluene diisocyanate, defoamer, chain extender and nano-interface modifier prepared in Step 1. Stir at high speed under constant temperature. Step 4, blending and dispersion: Pour the molten material obtained in step 3 into a mixing tank, add MDI and solubilizer, and stir continuously at 170-173°C to obtain a blended material; Step 5, conditioning and functionalization: Pour the blend material obtained in step 4 into the reaction tower, add graphite and zinc stearate, and perform bottom blowing stirring and heat preservation under argon protection to obtain the extrusion raw material; Step 6, Dynamic temperature-controlled extrusion molding based on online rheological feedback: The extrusion raw material prepared in step 5 is fed into a screw extruder equipped with an online rheometer and a near-infrared spectral sensor; the system dynamically adjusts the temperature of the extruder barrel section and the extrusion section according to the online monitored melt viscosity and component uniformity data; after preheating, screw extrusion is performed, and the final product is obtained after cutting.
7. The preparation process according to claim 6, characterized in that, The toluene diisocyanate is added in step three as a fast chain extender; the diphenylmethane diisocyanate (MDI) is added in step four as a long-chain compatibilizer / crosslinker.
8. The preparation process according to claim 6, characterized in that, The dynamic adjustment includes: the temperature of the barrel section is 165-168℃, the temperature of the extrusion section is 180-183℃, and the screw speed of the spiral extrusion is 150 r / min.
Citation Information
Patent Citations
Thermoplastic blending material and preparation process thereof
CN116656101A
